Citrulline and Nonessential Amino Acids Prevent Fructose-Induced Nonalcoholic Fatty Liver Disease in Rats. Issue 10 (5th August 2015) - Jegatheesan, Prasanthi; Beutheu, Stéphanie; Ventura, Gabrielle; Nubret, Esther; Sarfati, Gilles; Bergheim, Ina; De Bandt, Jean-Pascal
Abstract: Background: Fructose induces nonalcoholic fatty liver disease (NAFLD). Citrulline (Cit) may exert a beneficial effect on steatosis. Objective: We compared the effects of Cit and an isonitrogenous mixture of nonessential amino acids (NEAAs) on fructose-induced NAFLD. Methods: Twenty-two male Sprague Dawley rats were randomly assigned into 4 groups ( n = 4–6) to receive for 8 wk a 60% fructose diet, either alone or supplemented with Cit (1 g · kg −1 · d −1 ), or an isonitrogenous amount of NEAAs, or the same NEAA-supplemented diet with starch and maltodextrin instead of fructose (controls). Nutritional and metabolic status, liver function, and expression of genes of hepatic lipid metabolism were determined. Results: Compared with controls, fructose led to NAFLD with significantly higher visceral fat mass (128%), lower lean body mass (−7%), insulin resistance (135%), increased plasma triglycerides (TGs; 67%), and altered plasma amino acid concentrations with decreased Arg bioavailability (−27%). This was corrected by both NEAA and Cit supplementation. Fructose caused a 2-fold increase in the gene expression of fatty acid synthase ( Fas ) and 70% and 90% decreases in that of carnitine palmitoyl-transferase 1a and microsomal TG transfer protein via a nearly 10-fold higher gene expression of sterol regulatory element-binding protein-1c ( Srebp1c ) and carbohydrate-responsive element-binding protein ( Chrebp ), and a 90% lower gene expression of peroxisome proliferator-activated receptor α ( Ppara ). NEAA or Cit supplementation led to a Ppara gene expression similar to controls and decreased those of Srebp1c and Chrebp in the liver by 50–60%. Only Cit led to Fas gene expression and Arg bioavailability similar to controls. Conclusion: In our rat model, Cit and NEAAs effectively prevented fructose-induced NAFLD. On the basis of literature data and our findings, we propose that NEAAs may exert their effects specifically on the liver, whereas Cit presumably acts at both the hepatic and whole-body level, in part via improved peripheral Arg metabolism.